The pattern of self‐poisoning among Lebanese children and adolescents in two tertiary care centres in Lebanon - Sinno, Durriyah (2009)
Aim: Self‐poisoning in childhood and adolescence is a major problem for health authorities all over the world. The objective of this study was to determine the pattern of self‐poisoning in Lebanese children and adolescents. Materials and methods: This prospective study included all cases of poisoning in individuals aged 0–18 years who presented to the emergency department of two major hospitals in Beirut, Lebanon over a period of 1 year. Participants were divided into two age groups (0–12 years and 12–18 years). These cases were followed to record the applied treatment and whether the patient was admitted or discharged. Results: There were 110 self‐poisoning incidents, of which 74 (67%) were in female patients. The predominant type of poisoning was with pharmaceutical products (68.2%). Accidental self‐poisoning was significantly more common in the younger age group among both genders compared with the older age group (p < 0.0001). There were significantly more poisoned male children (72%) than male adolescents (28%) (p = 0.003); whereas among females, poisoned adolescents were significantly more common (64%) than poisoned children (36%) (p = 0.009). Moreover, poisoning with pharmaceuticals was significantly higher in the young male group compared to the older age group and older female group compared to the younger age group (p = 0.0007 and p = 0.01, respectively). In total, 78% of patients were discharged home following basic observation, charcoal or gastric lavage. Conclusion: Female adolescents are more at risk of deliberate self‐intoxication after the age of 12 years compared to males, whereas males younger than 12 years are more likely to suffer from accidental poisoning. Preventative strategies include screening adolescents at high risk of self‐harm in order to offer adequate counselling, while providing anticipatory guidance for parents of children in the younger age group.